Development of a Science Process Skills–Based Practicum Guide in the Science Subject to Improve Students’ Conceptual Understanding at MI Sabilillah Tanjung Kertosono Nganjuk - Nurul Mukaromah Dwi Hayati (PGMI, STAI Miftahul Ula Nganjuk, 2025)
In the field of education, science learning is a discipline that requires practicum activities for systematic verification. To achieve learning outcomes that encompass scientific products, processes, and attitudes, practicum activities are essential in science instruction. Based on the results of an interview with a Grade IV teacher, it was found that the madrasah does not yet have a specific practicum guidebook, resulting in students being less motivated and having difficulty understanding basic concepts when conducting science practicum activities. Therefore, appropriate teaching materials are needed. The suitable teaching material is a science practicum guide based on science process skills. The objectives of this study are: (1) to determine the feasibility of the science practicum guide in improving students’ understanding of science concepts at the madrasah level, and (2) to determine the effectiveness of the practicum guide in science learning. This study employed a Research and Development (R&D) method. The development model used was the 4-D model (Define, Design, Development, Disseminate). The research subjects were Grade IV students of MI Sabilillah Tanjung. Data collection methods included observation, interviews, and questionnaires. The data analysis technique used was descriptive quantitative analysis. The development process of the science practicum guide based on science process skills consisted of four stages: definition, product design, product development, and product dissemination. The feasibility and effectiveness of the science practicum guide based on science process skills were proven to be very high, with validation results from subject-matter experts at 92%, design experts at 93%, teacher responses at 85%, and student responses at 74%. The effectiveness result reached 78%, indicating that the guide is effective for use in the teaching and learning process, particularly in science practicum activities.